Professional patios, emotional studios : Locating social ties in European art residences - Basov, Nikita (Elsevier, 2025)
To foster creativity through sociality, residences put artists together. At the same time, in their quest for originality, artists often opt for individualism. Little is known on how physical collocation in residences affects artistic sociality. Addressing this gap, we draw on a combination of interviews, observations, and surveys, analysed with an innovative mixture of abductive coding, computational space analysis, and statistical network modeling. This allows us to unveil how room sharing and object usage relate to friendships and collaborations between residents. Along with explicit individualism of artists, we spot plenty of social ties between them. And these ties are positively related to joint material embeddedness. Simultaneously, the two main types of residential zones – working studios and leisure areas – appear to encourage the types of social ties inverse to our expectations. Our findings inform the practice of artistic residence organising and the proposed approach enables explanatory analysis of the relation between material space and sociality in various settings.